2022
DOI: 10.3390/soilsystems6010019
|View full text |Cite
|
Sign up to set email alerts
|

Litter Decomposition in Wet Rubber and Fruit Agroforests: Below the Threshold for Tropical Peat Formation

Abstract: Peatlands are shaped by slow litter decomposition, but threshold decomposition rates that allow peat formation remain unclear. Can agroforestry in the tropics be compatible with paludiculture that allows peat formation? We explored the determinants of litter decomposition in wet agroforests adjacent to tropical peatlands in Central Kalimantan (Indonesia) by litterbag studies (up to 16 weeks) with standing litter sources to estimate rate constants, characterize litter quality (especially lignin (L), polyphenoli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 82 publications
0
3
0
Order By: Relevance
“…For instance, to grow Aonla fruit, no additional input (water and fertilizer) was applied but yielded better than sole aonla plantation as well as middle-storied lemon also yielded better with no additional inputs [46]. Trees in crop fields have some advantages on crop productivity such as continuous deposition of mulch and nutrient-enriching topsoil [47]. Additional resources from trees such as fruits, firewood, timber and non-timber also add to the income table.…”
Section: Discussionmentioning
confidence: 99%
“…For instance, to grow Aonla fruit, no additional input (water and fertilizer) was applied but yielded better than sole aonla plantation as well as middle-storied lemon also yielded better with no additional inputs [46]. Trees in crop fields have some advantages on crop productivity such as continuous deposition of mulch and nutrient-enriching topsoil [47]. Additional resources from trees such as fruits, firewood, timber and non-timber also add to the income table.…”
Section: Discussionmentioning
confidence: 99%
“…Hu et al [10] used ADH to verify the litter Phosphorus content and the contribution of soil fauna in different environments to the HFA. Silvianingsih et al [51] calculated ADH and found that the decomposition rate caused by the HFA was 80% faster.…”
Section: Ongoing Debates Over the Existence Of The Hfamentioning
confidence: 99%
“…Measurements in an A. crassicarpa plantation on organic soils (also known as peatlands) showed slow litter decomposition due to a high lignin content (36%-39%), low P and N content (P < 0.25% and N < 2.5%), and unfavourable soil environment, microclimate conditions [144], and a poor soil microbe population [145]. In (agro)forests on the fringe of a peat dome, wet conditions slowed decomposition, but not enough to induce peat formation [146].…”
Section: Diversity In Litter Quality and Timing Vs Single-source Litt...mentioning
confidence: 99%